OSTEOPOROSIS AND C-REACTIVE PROTEIN - S G Anikin; L I Benevolenskaya; E N Aleksandrova; S G Anikin; L I Benevolenskaya; E N Aleksandrova (Научно-практическая ревматология)
A chronic inflammatory process is one of the risk factors of secondary osteoporosis (OP) and its related fractures. Determination of the level of C-reactive protein (CRP) is used to estimate the magnitude of an inflammatory reaction. The developed highly sensitive (hs) methods make it possible to reveal the so-called subclinical level of inflammation and to assess its role in the development of various diseases. Objective: To reveal an association between the level of hs CRP and the development of OP. Subjects and methods. The database of the study «Cardiovascular diseases and osteoporosis» performed at the Research Institute of Rheumatology, Russian Academy of Medical Sciences, was used. The study enrolled 79 women, of them 64 were postmenopausal and 15 had a preserved menstrual cycle. Their mean age was 60 and 48 years, respectively. The exclusion criteria were systemic rheumatic diseases and conditions, which are risk factors for OP, and drug therapy for OP. Bone mineral density (BMD), biochemical blood analysis, bone metabolism markers, and CPR levels were determined by the hs method. Results. In the postmenopause group, the mean value of hs CRP was 1.16 mg/l; the values of hs-CRP were in the range of 3-10 mg/l in 17% cases, which is associated with subclinical inflammation. Those of CRP were lower than 3 mg/l in 80% of cases. In 87% of the women with a preserved cycle, the level of CRP was in the normal range and averaged 2.25 mg/l. There was a positive correlation of hs CRP only with the level of bone alkaline phosphatase (r = 0.26; p = 0.04) in the menopause group and with BMD in the femoral neck (r = 0.65; p = 0.009) in the preserved cycle group. There were no significant differences in the level of hs-CRP between the OP subjects and the normal values of BMD in the menopausal women. No analysis was made in the preserved cycle subgroup due to a small number of cases. Conclusion. There was no strong evidence that there was an association between hs CRP (the values were in the normal range and corresponded to those of subclinical inflammation) and osteoporosis.